2017
DOI: 10.1002/cbdv.201600441
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Baobab Seed and Its Relationship with the Genus Adansonia Taxonomy

Abstract: Baobab seed oil contains specific fatty acids. Most of the studies on baobab fatty acids have been carried out singly and in isolation from each other, making it difficult to compare results through different species. The objective of the present study is to establish the seed fatty acid composition of each Adansonia species in order to evaluate and understand the relationships between the oil chemical compositions, the baobabs' taxonomy and, the ecological and geographical origin of each seed lot. The seed oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The compositions of palmitic, oleic, and linolenic fatty acids were higher compared to the compositions of other fatty acids. The higher fatty acid compositions of the baobab crude oil in this study were in the ranges of previous studies [ 9 , 41 ]. It has been reported that as healthy fats, linoleic and oleic acids maintain cell membranes which provide energy and offer vitamin E which is a powerful antioxidant [ 32 , 55 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The compositions of palmitic, oleic, and linolenic fatty acids were higher compared to the compositions of other fatty acids. The higher fatty acid compositions of the baobab crude oil in this study were in the ranges of previous studies [ 9 , 41 ]. It has been reported that as healthy fats, linoleic and oleic acids maintain cell membranes which provide energy and offer vitamin E which is a powerful antioxidant [ 32 , 55 ].…”
Section: Discussionsupporting
confidence: 80%
“…The Malvaceae family has seed oil that contains essential fatty acids including palmitic, oleic, linolenic, and cyclic fatty acids (cyclopropene fatty acids) [ 9 ]. It has been reported that cyclopropene fatty acids are often accompanied by a smaller proportion of cyclopropanic fatty acids such as dihydrosterculic and dihydromalvalic acids, which are the dihydro analogues of cyclopropene fatty acids [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the growth rate was observed with oil concentration increased until the growth of phytopathogens was stopped when submitted to their respective MICobs (See Table 1), there was a significant difference in the negative controls that showed the highest growth According to literature, the phenolic compound Eugenol is the major constituent of clove essential oil, in addition to other chemical compounds such as β-caryophyllene, αhumulene, caryophyllene oxide and eugenyl acetate in lower concentrations [21,22,34,35]. The fungitoxicity of eugenol and other compounds has been reported in some studies [26,35,36,37].…”
Section: Means Of the Index Of Mycelial Growth Speed (Cm Day -1 ± Sd)mentioning
confidence: 96%
“…The properties of clove (Syzygium aromaticum L.) essential oil been studied by several investigators and their biological activities, including antifungal activity, have been documented on literature. Its main constituents are eugenol (70-90%), eugenol acetate (5-15%) and β-caryophyllene (up to 2.1%) [21,22]. Many studies documented their effective use in the control of Rhizoctonia solani [23] and Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%
“…7 The baobab product is used for 17 medicinal uses, 7 food uses, and 1 construction uses. 9 The baobab species have been known to provide shade, edible fruits, resins, aesthetic sight, gums, pharmaceutical product, tannins, oils and leaves. 10 The socio-economic importance of the species is highest because the tree is used for various purpose.…”
Section: Introductionmentioning
confidence: 99%